TIC’S en la educación - Chiscueth Portilla, Pamela Eliana (2016)
The current world society changes its way of living according to its needs, so it uses of that access, and education is a baseline for human transformation. For that reason present research project is based on the use of the technologies within the hours of classes from the educational community, as an important pedagogical tool for the strengthening of the curricular activities. At the Educational Unit "Victoria Vásconez Cuvi", "Elvira Ortega", morning section, was the lack of information and communication technologies was observed in the inter-learning process implementation as part of a well-rounded education, so it is necessary to implement educational, pedagogical and didactic development that contribute to the country in the social, cultural, economic, political, changes among others. By what is should promote a technical training of teaching through the essential materials for the application of new educational models in favor of the students with the implementation of the necessary technological equipment. However the traditionalism of a group of teachers, does not allows a domain of online tools of the classroom, because even is apply old processes to the change of age, where the attention of the students are links to innovative equipment. In this way the diagnostic of the use of ICT’s in the educational environment, through the use of research processes, coming to techniques and instruments of data collection, to strengthen our knowledge on the subject, will form the basis of departure to the purpose pursued by this project, to research the management in education, with the help of an empirical approach that will facilitate the getting of information about its utility; which we will make an analysis and interpretation of the information obtained through it tab of results that determine conclusions and recommendations, of the work made along this time, as result of the made work will be of a contribution training for possible research of the theme.